The study of serum c-reactive protein and its diagnostic importance in reducing the rate of negative appendectomy - Kumari, Bandana; Kumar, Pawan; Chaudhary, Neha; Kumar, Anil; Roy, Achal Narain (International Journal of Research in Medical Sciences, 2017)
Background: Introduction-Acute appendicitis is the most common abdominal surgical emergency and appendectomy is one of the most frequently performed abdominal operation but the diagnosis of acute appendicitis remains an enigmatic challenge, plagued by high rate of negative exploration. The objective of this study was to assess the accuracy of CRP over TLC in the diagnosis of acute appendicitis. Methods: Total 200 patients who had been diagnosed as a case of acute appendicitis based on WBC count and clinical diagnosis and were planned for appendectomy were selected for purposive sampling. Serum CRP was estimated in these patients before operation but was not considered in decision making process of appendectomy. All 200 removed appendixes were sent for histopathological examination. Results: Result-Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of serum CRP were much greater than WBC count. Mean and standard deviation of serum CRP was 41.92±26.28 with p=<0.0001 which is highly significant. Conclusions: Conclusion-CRP should be added along with clinical diagnosis and other laboratory test in diagnosis of acute appendicitis to reduce the rate of negative appendectomy.